1997
DOI: 10.1002/(sici)1096-9071(199701)51:1<6::aid-jmv2>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous response for a mammalian hepadnavirus infection to acyclovir: Drug-arrested intermediates of minus-strand viral DNA synthesis are enveloped and secreted from infected cells as virion-like particles

Abstract: Three woodchucks infected persistently with the woodchuck hepatitis virus (WHV) were treated with acyclovir (ACV) to investigate the effect of inhibiting viral DNA synthesis upon the replication of an orthohepadnavirus in vivo. Normal viraemia was reduced during the treatment period in all three animals, but each responded with a distinct serum phenotype. In the most provocative case, the profile of the WHV DNAs in both the liver and serum provided a simple and novel description of the orthohepadnaviral infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…In contrast to the established dogma of preferential virion secretion of mature genome for wild-type (WT) hepadnaviruses (17,33,40,44,47,48), the 97L mutation results in secretion of virions containing an immature genome into the medium and is characterized by excessive amounts of minus-strand DNA (47,48). Even though the immature secretion phenotype has been observed with woodchuck and snowgoose hepadnaviruses (7,42), it has not been reported with human patients. This may be due to the presence of naturally occurring compensatory mutations for 97L in the core protein at positions 5 (11) or 130 (49), both changing a highly conserved proline to threonine.…”
Section: Hepatitis B Virus (Hbv) Is a Major Human Pathogenmentioning
confidence: 88%
“…In contrast to the established dogma of preferential virion secretion of mature genome for wild-type (WT) hepadnaviruses (17,33,40,44,47,48), the 97L mutation results in secretion of virions containing an immature genome into the medium and is characterized by excessive amounts of minus-strand DNA (47,48). Even though the immature secretion phenotype has been observed with woodchuck and snowgoose hepadnaviruses (7,42), it has not been reported with human patients. This may be due to the presence of naturally occurring compensatory mutations for 97L in the core protein at positions 5 (11) or 130 (49), both changing a highly conserved proline to threonine.…”
Section: Hepatitis B Virus (Hbv) Is a Major Human Pathogenmentioning
confidence: 88%
“…We further reported that this immature secretion phenotype can be rescued intramolecularly by a proline-tothreonine mutation at amino acid 130 (P130T) in the core protein (72) or intermolecularly by an alanine-to-phenylalanine mutation at amino acid 119 (A119F) in the large envelope protein (37). An immature secretion-like phenomenon was also observed in vivo in animal models (9,63). Although the immature secretion phenomenon of mutant 97L can be observed in both the adr and ayw subtypes, the mutation occurs frequently in subtype adr (1,5,14,15,16,17,21,29,33,61,64,65) but rarely in subtype ayw (40,41,48).…”
mentioning
confidence: 86%
“…Although an immature secretion-like phenotype has also been found to occur in vivo in woodchuck and snow goose hepadnaviruses (4,26), it is puzzling that it has not been found so far in natural infection in humans (F. M. Suk, M. H. Lin, and C. Shih, unpublished results). Furthermore, it remains unclear whether an immature secretion phenotype can still be observed in the genetic context of naturally occurring variants, which often contain multiple mutations throughout the genome.…”
mentioning
confidence: 96%